A rational approach to migraine diagnosis and management in primary care. (1st January 2021) - Martin, Vincent T.; Feoktistov, Alexander; Solomon, Glen D.
Abstract: Migraine is a chronic neurologic disease estimated to affect approximately 50 million Americans. It is associated with a range of symptoms, which contribute to disability and substantial negative impacts on quality of life for many patients. Still, migraine continues to be underdiagnosed, undertreated, and optimising treatment for individual patients has proven difficult. As many migraine patients will be seen first in primary care settings, internists and other primary care providers are ideally positioned to improve diagnosis and migraine management for many patients. In this review, we discuss some of the challenges in diagnosing migraine and suggest strategies to overcome them, summarise the current understanding of migraine pathophysiology and clinical evidence on acute and preventive treatment options, and offer practical approaches to diagnosis and contemporary management of migraine in the primary care setting. Key messages: Migraine is a prevalent disease with substantial impact. Primary care providers are ideally positioned to improve care for migraine patients with streamlined approaches to diagnosis and management. A stepwise diagnostic approach to migraine involves taking a thorough headache history, excluding secondary headache, and identifying primary headache disorder using screening tools or ICHD-3 criteria. The FDA approved seven new migraine therapies from 2018 to 2020 (four monoclonal antibodies, two gepants, one ditan), expanding acute and preventive therapeutic options.